Cinnamon Oil as an Antibacterial Agent on Natural Paper from Banana Peel (Musa paradisiaca Linn.) - Widiastuti Agustina Eko Setyowati; Elfi Susanti VH; Iis Alviah; Melati Kusuma Wardani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
The research about the use of cinnamon oil as an antibacterial agent on natural paper from Banana (musa paradisiaca Linn.) Peel has been conducted. The preparation of the paper using alkalization method, with the use of NaOH 4% at the temperature of 100oC for 1.5 hours. The paper is made in two variations, ie with additive cinnamon oil and without additive. The natural paper produced are tested for pH based on SNI ISO 6588-1.2010 and water content by dry-oven method based on SNI ISO 287:2010. The antibacterial activities were tested against Staphylococcus aureus and Escherichia coli using Kirby-Bauer disc diffusion method. The paper produced meet the standard of ISO 6519:2016 about Basic Paper for Laminated Plastic Wrapping Paper within the parameter of pH and water content. The results showed that the paper with additive cinnamon oil have antibacterial activity againts S. aureus and E. coli with inhibition diameter zone 15 mm and 13 mm respectively, whereas paper without cinnamon oil additives has no antibacterial activity against either S. aureus or E. coli. These result indicate that cinnamon oil can be used as an antibacterial agent on the natural paper from Banana peel (musa paradisiaca Linn.).